Layout design for the outpatient smart pharmacy - Yan, Wenbin (2019)
In the past industrial has shift from craft production to mass production, with growing demand on production and complexity of industrial, we have further transformation to meet out new demand. The industrial 4.0 has been introduced to shift centralized control to decentralized with communication through internet as a powerful instrument to control distributed system and using Radio Frequency Identification Devices (RFID) system to keep tracking on individual product[1]. The Industry 4.0 can be divided into three sectors: The first is “smart industry”, focusing on the intelligent production and product processes, and the machine are able to processing the data on this own and self-preforming certain task as well as interact with human; The second is “intelligent production”, which involves production logistics management, human-computer interaction and application of 3D technology in industrial production. The third is “smart logistics”, which mainly integrates logistics resources through the Internet, from logistics network it controls existing logistics resource supplier to increase efficiency[1, 2]. Smart pharmacy is part of the smart industry, focusing on the intelligent dispensing and process, by automating 80% of the medication dispensing workflow with decreased the rework rate, hence enables pharmacies o handle high prescription loads and efficiently, as well as improves manual picking accuracy for certain drugs[3].